Modernisasi Warisan : Sebuah Pendekatan Penciptaan Nilai Bersama untuk Inovasi Produk dan Daya Tahan Merek pada Usaha Kuliner Tradisional - Deddy Ray Girsang (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Culinary businesses that rely on cultural heritage are faced with a core challenge: aligning the need for innovation to remain competitive with the need to maintain the authenticity that is the essence of the brand. This study investigates the potential application of the concept of value co-creation as a strategic model to address the conflict between innovation and authenticity. Using a comparative qualitative case study method on four culinary MSMEs in Medan, Indonesia, this research found that authenticity can act as a "golden confinement" that protects as well as inhibits renewal. Through in-depth interviews, participatory observations, and documentation analysis, this study identifies the dynamics of the relationship between business owners, consumers, and the cultural identity inherent in the product. Key results indicate that the implementation of value co-creation, particularly by involving loyal consumers in their dual function as "guardians of tradition" and "changemakers", is a vital mechanism for addressing this dilemma. Consumer involvement in the product development process allows companies to remain relevant without losing their traditional characteristics. Furthermore, the study emphasizes the importance of formalizing the co-creation process—transforming informal dialogue into documented, measurable strategic data. Thus, the innovation process is no longer ad-hoc, but rather structured and rooted in the shared aspirations between producers and consumers. This strategy allows businesses to evolve authentically, maintaining cultural roots while still responding to changing market dynamics. This research contributes by presenting a participatory innovation model that can be implemented by tradition-based businesses, especially in the context of creative economy and sustainable local cultural preservation. This model also opens up opportunities for cross-sectoral collaboration to drive cultural transformation through a more inclusive and adaptive approach.